Regulation of Cell Signaling Pathways by Genistein in Different Cancers: Progress, Prospects and Pitfalls - Mobeen, Iqra; Romero, Mirna Azalea; Yulaevna, Ishmuratova Margarita; Attar, Rukset; Jabeen, Saima; Fayyaz, Sundas (Cellular and Molecular Biology, 2022)
On the translational front, integrative genomic approaches have spurred the identification of diverse mechanisms of drug resistance, tumor heterogeneity, metastasis and emerging preclinical targets. Recent breakthroughs in oncogenic cell signaling pathways have forged new links and multi-disciplinary researchers have unraveled different facets of signaling landscapes. Natural product research has witnessed breakneck developments mainly in the context of the ever-expanding list of bioactive components having significantly pharmacological properties. Genistein has gradually gained appreciation because of its multifaceted roles in the prevention and inhibition of carcinogenesis and metastasis. More importantly, the entry of genistein into various phases of clinical trials substantiates the medicinal and pharmacological significance of genistein in cancer chemoprevention. In this review, we have attempted to summarize how genistein regulated different oncogenic pathways in carcinogenesis and metastasis. Furthermore, genistein-mediated regulation of non-coding RNAs is also an interesting feature that has been included in this review to realistically analyze how genistein-mediated control of miRNAs, lncRNAs and circRNAs influence carcinogenesis. In the later sections, we have provided a summary of clinical trials related to genistein for cancer prevention/inhibition. However, apart from the optimistic approaches to further investigate genistein-mediated cancer-inhibitory effects, certain hints have emerged which underscore the pro-metastatic role of genistein. Therefore, the pro-metastatic role of genistein in different cancers should be rationally tested in a broader context because these properties in the future may reduce the enthusiasm in the quest to pursue genistein as a potent cancer chemopreventive agent.